Language management and devolved governance in Kenya. Issue 2 (3rd July 2017) - Mwaniki, Munene
Abstract : The article explores interfaces between language management and devolved governance in Kenya against the backdrop of language management theory and the roles and responsibilities of devolved governance as defined by traditional fiscal federalism, new public management (NPM), public choice, new institutional economics (NIE), and network forms of local governance. This discussion establishes theoretically sound intersections between language and devolved governance, underpinned by the centrality of language in information and knowledge access, sharing and utilisation in governance processes and structures. The article applies this proposition to the language and devolved governance interface in Kenya and identifies engendering active citizenship, accountability and transparency, and mainstreaming indigenous knowledge into governance and development discourses as some of the interfaces between language management and devolved governance in Kenya. The article argues that language management is integral to the optimisation of devolved governance that is responsive, responsible and accountable in Kenya, and possibly elsewhere.